Moral Universalism: Measurement and Heterogeneity - Benjamin Enke; Ricardo Rodríguez-Padilla; Florian Zimmermann (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper introduces a new set of simple experimentally-validated survey games to measure moral universalism: the extent to which people exhibit the same level of altruism and trust towards strangers as towards in-group members. In a representative sample of the U.S. population, an individual's degree of universalism is largely a domain-general trait. Older people, men, whites, the rich, the rural, and the religious exhibit less universalist preferences and beliefs. Looking at economic behaviors and outcomes, universalists donate less money locally but more globally, are less likely to exhibit home bias in equity and educational investments, have fewer friends, and report being more lonely.
Keywords: 330; moral universalism; in-group bias